2017
DOI: 10.29252/johe.6.3.136
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mortality among road accident victims in the south of Kerman Province, Iran, from 2012 to 2015

Abstract: Background: Road accidents and their resulting deaths are important issues in the Iranian society. Identifying the distribution of mortality as a result of road accidents has a significant role in preventing this problem. The aim of this study was to investigate the frequency of road deaths in Southern Kerman Province, Iran, from 2012 to 2015. Materials and Methods: In this cross-sectional study, the injured individuals who died due to road accidents were entered into the study by census sampling method. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A study conducted in the United States showed that the severity of accidents was higher in autumn and in winter than in spring (9). According to the studies conducted in the south of Kerman, the highest rate of mortality was in spring and in autumn (22). Another study in Rafsanjan, Iran, demonstrated that the highest and the lowest rates of accidents were in autumn and in winter, respectively (23).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the United States showed that the severity of accidents was higher in autumn and in winter than in spring (9). According to the studies conducted in the south of Kerman, the highest rate of mortality was in spring and in autumn (22). Another study in Rafsanjan, Iran, demonstrated that the highest and the lowest rates of accidents were in autumn and in winter, respectively (23).…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent reports, every year global road traffic deaths are estimated to be 1.2 million and between 20 and 50 million suffer from non-fatal injuries [3]. In Iran, according to the latest statistics released by the Forensic Medicine Organization, traffic crashes cause nearly 17000 deaths each year and a permanent injury or disability for 300000 people [4].…”
mentioning
confidence: 99%